(Re)Acting (to) the crisis: A comparative analysis of crisis framing in obesity, climate change, antimicrobial resistance, and the UK cost-of-living crisis - Kathrin Lauber; Nason Maani; Olivia Brown; Rebecca Glover (Journal of Critical Public Health)
Across human and planetary health, the concept of crisis provokes a sense of exceptionalism and sudden diversion from a supposed 'normal' state of affairs. By approaching crises as socially constructed rather than objectively occurring phenomena, we open up paths of enquiry that can help us to understand what it means to promote, use, or suppress the framing of an issue as a crisis. Actors can create or exploit crisis narratives to define the crisis and specific solution(s) in their interest. Identifying and critically interrogating different crisis framings, however, represents a key challenge. In this paper, we analyse four case studies from across human and planetary health: obesity, climate change, antimicrobial resistance, and the cost-of-living. Adopting an interpretive lens to interrogate these ‘crisis imaginaries’, we interrogate how crises are constructed through, and reflected in, discourse. We build on existing frameworks to better develop methods to critically evaluate crisis conceptions and understand how these may drive (and be driven by) the commodification of narratives in public health. In paying particular attention to power dynamics, we demonstrate how crisis narratives may obscure longstanding inequities. We conclude by providing recommendations to better inform consideration of the drivers, trade-offs, and wider implications of crisis framing.